Manipulating anthracyclines for deeper tissue penetration and implications for glycolytic tissues - Erik R. Abels; Esther ter Linden; Jos H. T. Rohling; Lennard M. Voortman; Dennis P. A. Wander; Lennert Janssen; Marten Hornsveld; Herman S. Overkleeft; Sabina Y. van der Zanden; Marike L. D. Broekman; Jacques Neefjes (Proceedings of the National Academy of Sciences, 2025)
How drugs penetrate tissues is poorly understood yet important, since drugs that fail to reach their target will be ineffective. We followed the fate of anthracycline cancer drugs at high resolution by exploiting their intrinsic fluorescence. In a cell-based spheroid model, the soluble compound fluorescein penetrates the entire spheroid, unlike hydrophobic fluorescent lipids, which only enter the outermost cell layer. Anthracyclines have intermediate hydrophobicity. They enter the nucleus of a few outer cell layers at neutral pH, but penetrate the spheroids more deeply under acidic conditions, with a reduction in cell entry and cytotoxicity. The glycolytic conditions that prevail in the tumor microenvironment may thus limit cell entry and contribute to anthracycline drug resistance. We evaluated a library of anthracycline variants to determine the physicochemical properties related to tissue penetration depth. We find that this is determined by only three chemical properties: molar refractivity, topological polar surface area, and water solubility. Our findings suggest that modifications of anthracyclines may improve access and activity to deeply tissue-embedded targets such as pancreatic cancer.